(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Floating testing platforms and marine energy devices use Dynamic Power Cables (DPC) to connect to the testing centres or the national grids. These power cables are, therefore, an inherent component in the reliable operation of the floating structure, and their integrity throughout the design life of the device should be ensured from the early stages of the project. Fatigue failure is one of the most common factors affecting the cable’s performance due to the cyclic loads caused by waves and currents. However, accurately estimating the fatigue life of DPC has proved challenging due to their material and geometric nonlinearities. In addition to fatigue failure, the cable design life is also characterised by its ability to withstand extreme conditions on-site. This paper addresses the design, analysis and specification of a dynamic power cable that will be deployed at the Biscay Marine Energy Platform (BiMEP) for the connection of the HarshLab 2.0, a floating testing platform for materials, subsystems and components developed and operated by Tecnalia. BiMEP is exposed to severe waves that induce large motions on the HarshLab buoy, and different numerical models for the analysis of the hydrodynamic response are reviewed and calibrated against model tests. To address a comprehensive study of the power cable at the design stage, this paper focuses on reviewing different fatigue-life prediction methods employed for a DPC, considering the damage in the steel armour and the conductor cores. It also covers the cable’s response when the system operates under extreme sea conditions and the potential implications of sensitive variables such as loss of buoyancy and marine growth. To perform the fatigue-life study, long-term cyclic loading in each cable component was compared with its resistance to fatigue damage. In this case, the damage for each variable was derived from stress- and strain-based curves for the high-strength steel (armour) and the copper (core conductor) depending on the selected approach. The design iterative process using the studies performed in this paper led to the definition of a Lazy Wave design with a high-level optimisation of some components, e.g. the ballast and buoyancy modules and the bend stiffener. In general, the behaviour across the cable length is similar between the different fatigue-life approaches, with the most significant expected fatigue damage found in localised hot spots near the bend stiffener and the belly (sag-bend region) of the cable, before the buoyancy modules. It is found that, despite a significant difference across the magnitude of fatigue life estimated in sensitive areas, the final design complies with all design criteria and reaches a satisfactory fatigue life.